DEVELOPMENT OF BLUETOOTH BASED PICK AND PLACE ROBOT VEHICLE FOR INDUSTRIAL APPLICATIONS - Surao, Anuj (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The increase of human needs is increasing, even it has pushed the robotics sector to evolve even more. Pick and place robots are becoming increasingly important in industries, even they perform specialized tasks instead of humans. They are designed to handle various tasks precisely. It reduces production costs in industries. This work includes a robot arm that can move in all directions. This allows it to work in small spaces and pick up items from various angles. The gripper on the arm handles various directions. A Programmable Logic Controller (PLC) ensures smooth, accurate pick and place robotic arm operation. Therefore, by using Bluetooth robot will move in all directions. Hence, this development of bluetooth based pick and place robot vehicle for industrial applications will reduce cost, work accurately and time saving.